KAJIAN DAUN KEMANGI (Ocimum Bacillium) SEBAGAI BACTERIAL DEACTIVATED AGENT (BDA)PADA SINTESIS SABUN CAIR CUCI TANGAN DARI MINYAK JELANTAH - Siti Fatimah; Satria Nur Wardhana (Jurnal Ilmiah Teknosains, 2019)
Waste cooking oil is oil that used in household needs that have been used repeatedly and some are not suitable for consumption anymore. Waste cooking oil contains carcinogenic substances that harm the body because it can cause cancer, narrowing of blood vessels that trigger coronary heart disease, stroke, hypertension. The innovation of processing used cooking oil is another product, one of which is soap making. The method that can be used is the Carbon Activated Agent (CAA) saponification process, where activated carbon is used as the neutralizing agent. CAA material combined with ocimum bacillium leaf extract in the process of making this soap can be an antiseptic substance. Ocimum bacillium leaves as a bacterial deactivated agent (BDA) have 4 dominant compounds, namely linalool, geraniol, sitral, and eugenol which function as antiseptics. The variables used in this study included variations in the addition of basil leaf extract as BDA (10%, 14%, 18%) and variations in the ratio of the amount of added KOH (20 mL, 30 mL, and 40 mL). The results showed that the addition of 18% basil extract and with the addition of KOH by 30 mL gave the greatest inhibition of bacterial growth of 1.9 cm.